Evaluating the dimensionality of an instrument for measuring the factors affecting academic performance of international business students in project management modules. Issue 1 (1st May 2019) - Yousef, Darwish Abdulrahamn
Abstract : Purpose: This study aims to evaluate the dimensionality of an instrument developed by Lebcir et al. to measure the impact of teaching style, English language and communication skills and assessment methods on the academic performance of international business students in project management modules. Design/methodology/approach: Data were collected from two independent samples drawn from the United Arab Emirates (UAE); the first sample consisted of 581 undergraduate business students from a public higher education institution, while the second sample consisted of 188 undergraduate business students from a private higher education institution. Confirmatory factor and principal component analyses were employed; additionally, Cronbach's alpha was used to test the internal consistency of the instrument. Findings: The results showed that for both samples, the validity of measurement of all three factors by Lebcir and colleagues instrument was not confirmed. Therefore, caution should be taken when using this instrument, at least in Arab settings. Research limitations/implications: The present study has a number of limitations. The statistical techniques used in the present study might not be sufficient to judge the validity of Lebcir et al. 's (2008) instrument. For example, test-retest technique could be used to test the reliability of this instrument. This study has a number of implications, one of which is that those administrators who intend to use the recommendations of research works based on the three factors of Lebcir et al. 's (2008) instrument in Arab settings should be cautious, as such recommendations might be misleading in such settings. Originality/value: The present study is the first attempt to validate Lebcir et al. 's instrument in an Arab setting.